STRATEGY OF MANAGEMENT ORGANIZATION - S. Ya. PODOPRIGORA; V. V. KOSHELEV (Advanced Engineering Research)
The article is devoted to the philosophical aspects of the problem strategy of management organization, which bank human potential is conceptions; inculcate new technology and experience advanced; to the complex plane strategy of the suppose effectual work organization that are gain prime result of an competition.